The Role of Gender on Consumer Attitudes toward Multiple Celebrity Advertisements - Işık Özge YUMURTACI (Gaziantep University Journal of Social Sciences, 2013)
Although its has been widely used in advertising, the impact of multiple celebrity endorsement on consumers has not been known. Therefore, the aim of this study is to examine whether consumers’ attitudes towards advertisement and brand, and their purchase intention differ regarding to the gender of consumers in multiple celebrity endorsement. Hence, survey study was conducted with 256 individuals. The findings of this study indicates that when two celebrities are used in an advertisement, based on the consumers’ attitudes towards the celebrities, the attitudes towards advertisement and brand, and purchase intentions may show discrepancies according to the gender of consumers. This study may shed light on how to use multiple celebrities in companies’ marketing strategies in a more accurate and effective way while considering consumer gender differences